2013
DOI: 10.1016/j.jas.2012.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Airborne laser bathymetry – detecting and recording submerged archaeological sites from the air

Abstract: A new generation of airborne bathymetric laser scanners utilises short green laser pulses for high resolution hydrographic surveying in very shallow waters. The paper investigates its use for the documentation of submerged archaeological structures, introducing the concept of airborne laser bathymetry and focussing on a number of challenges this novel technology still has to face. Using this method, an archaeological pilot study on the northern Adriatic coast of Croatia has revealed sunken structures of a Roma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 35 publications
(42 reference statements)
0
47
0
Order By: Relevance
“…Within the water body, the laser beam is further spread due to the optical properties of water. As a consequence, the illuminated portion of the bottom increases as does the uncertainty in depth estimation (for a more detailed discussion, see Doneus et al, 2013.…”
Section: Airborne Laser Bathymetrymentioning
confidence: 99%
“…Within the water body, the laser beam is further spread due to the optical properties of water. As a consequence, the illuminated portion of the bottom increases as does the uncertainty in depth estimation (for a more detailed discussion, see Doneus et al, 2013.…”
Section: Airborne Laser Bathymetrymentioning
confidence: 99%
“…As a further application ALB was applied to map submerged archaeological structures over large areas in high detail. The results showed that the technique is mature enough to be utilized for underwater heritage management [10]. In combination with side-scan sonar, shipwrecks were indentified and their dimensions could be measured [11].…”
Section: Airborne Laser Bathymetrymentioning
confidence: 99%
“…agricultural land, pastures, woodland, shallow water - Doneus and Briese, 2011;Gaffney et al, 2012;Trinks et al, 2012;Doneus et al, 2013a). These systematic surveys usually result in a large number of archaeological sites.…”
Section: Introductionmentioning
confidence: 99%